Social Construction of Junior High School Social Studies Teachers in Kudus Regency on the Merdeka Curriculum - Fikri, Rizal Haikal; Astuti, Tri Marhaeni Pudji; Lestari, Puji (Journal of Educational Social Studies, 2025)
The Merdeka Curriculum brings challenges for social studies teachers in adjusting learning. The meaning of the teacher's social construction is a research gap that can be studied in facing this challenge. This study examines the social construction of junior high school social studies teachers in Kudus Regency in understanding the Merdeka Curriculum using Peter L. Berger's Social Construction Theory. The method used in this research is a qualitative method with the data source obtained from Grade VII & VIII Social Studies Teachers, Principal, and Vice Principal for Curriculum at SMP NU Putri Nawa Kartika. Data collection techniques used in this research are interviews and documentation. The results showed that three stages of social construction shape the meaning of the Merdeka Curriculum. Externalization can be seen from the teacher's adaptation in understanding and implementing the curriculum. Objectivation appears through institutionalizing the principles of the Merdeka Curriculum into learning practices. Internalization shows deep meaning that develops gradually, forming teachers' professional beliefs and practices.